Best practices in healthcare services quality improvement in neonatal intensive care unit (NICU) - Agapi Simeonidou; Paraskevi Karagianni; George Tsiotras (Ene, 2018)
The global economic crisis has forced states to take some measures to consolidate healthcare systems and implement policies that are forming a safety net for the provision of high quality healthcare services. International clinical protocols and guidelines could be useful enough for every part of a healthcare system. The main purpose of this review is to present the framework of quality improvement in healthcare services, as it is implemented in a neonatal intensive care unit (NICU) in Νorthern Greece and worldwide. A literature review of papers on implementation of good practices, as well as the efforts for continuing quality improvement in NICUs worldwide was performed. Although much progress has been achieved in neonatal care through continuous improvement of the quality of care, certain elements of the process still need to be addressed. It is important that continuous improvement programmes are major part of the care delivered in NICUs, with the participation of personnel, in total, parents and hospital administration.